Republic of Slovenia : 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Slovenia. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that inflation and the current account deficit in Slovenia are expected to moderate. The main downward risks to growth are lower-than-projected growth in Europe, and a credit crunch in the event that foreign financing of domestic banks dries up. In the medium term, the main challenge is that the economy needs to emerge from the global crisis on a sustainable growth path. Executive Directors have commended the authorities for their swift and decisive policy responses to slower growth and financial sector strains.